World no-tobacco: effects of second-hand smoke (SHS) and vapors on the developing and adult brain - Kisby, Glen; Raber, Jacob (Frontiers in Pharmacology, 2025)
The goal of this review is to highlight the role of second-hand smoke (SHS) or environmental tobacco smoke (ETS) and e-cigarette (EC) vapors on brain integrity and function during development and adulthood, including how it relates to increasing the risk for age-related neurodegenerative disorders. A systematic review of the literature of the effect of SHS or ETS and e-cigarette vapors on the brain revealed a total of 284 or 372 publications and 312 publications, respectively. After taking into account duplicate publications or publications focused on policy, surveys or other organs than brain, there are limited studies on the effects of SHS, ETS or EC vapors on brain structure and function. In this review, we examine the major constituents in SHS or EC vapors and their effects on brain health, mechanisms by which SHS or vapors alters brain integrity and function, including behavioral and cognitive performance. We hope that this review will encourage investigators to explore further the short-as well long-term effects of SHS or vapor exposure on the developing and adult brain to better understand its role in neurodevelopmental disorders and neurodegenerative diseases and ultimately to develop therapeutic modalities to reduce or even prevent the short- and long-term detrimental effects on brain health.